Expression of Sucrose Transporter cDNAs Specifically in Companion Cells Enhances Phloem Loading and Long-Distance Transport of Sucrose but Leads to an Inhibition of Growth and the Perception of a Phosphate Limitation - Dasgupta, Kasturi (American Society of Plant Biologists, 2014)
Sucrose (Suc) is the predominant form of carbon transported through the phloem from source to sink organs and is also a prominent sugar for short-distance transport. In all streptophytes analyzed, Suc transporter genes (SUTs or SUCs) form small families, with different subgroups evolving distinct functions. To gain insight into their capacity for moving Suc in planta, representative members of each clade were first expressed specifically in companion cells of Arabidopsis (Arabidopsis thaliana) and tested for their ability to rescue the phloem-loading defect caused by the Suc transporter mutation, Atsuc2-4. Sequence similarity was a poor indicator of ability: Several genes with high homology to AtSUC2, some of which have phloem-loading functions in other eudicot species, did not rescue the Atsuc2-4 mutation, whereas a more distantly related gene, ZmSUT1 from the monocot Zea mays, did restore phloem loading. Transporter complementary DNAs were also expressed in the companion cells of wild-type Arabidopsis, with the aim of increasing productivity by enhancing Suc transport to growing sink organs and reducing Suc-mediated feedback inhibition on photosynthesis. Although enhanced Suc loading and long-distance transport was achieved, growth was diminished. This growth inhibition was accompanied by increased expression of phosphate (P) starvation-induced genes and was reversed by providing a higher supply of external P. These experiments suggest that efforts to increase productivity by enhancing sugar transport may disrupt the carbon-to-P homeostasis. A model for how the plant perceives and responds to changes in the carbon-to-P balance is presented.